Exosomal miR-34b-5p from Bone Marrow Mesenchymal Stem Cells Attenuates Spinal Cord Injury via MAPK/PI3K/ AKT Pathway Modulation - Cheng, Ming; Jia, Long; Yang, Tao; Zhou, Xue; Zeng, Ling; Lu, Hua; Wen, Nianchi; He, Benxiang (Indian Journal of Pharmaceutical Education and Research, 2018)
Introduction: Bone Marrow Mesenchymal Stem Cells (BMMSCs) promote Spinal Cord Injury (SCI) recovery via exosomes containing bioactive molecules. This study examined the role and mechanisms of BMMSC-derived exosomes overexpressing microRNA-34b-5p (miR-34b-5p) in neuronal repair after SCI. Materials and Methods: BMMSCs were isolated from four 4-week- old Sprague-Dawley rats and introduced to miR-34b-5p mimics or Negative Controls (NC), after which exosomes were extracted and characterized. Twenty-four six-week-old SD rats were assigned to four groups, with 6 rats in each group: Sham, SCI, SCI+NC mimics Exos, and SCI+miR-34b-5p mimics Exos groups. SCI was induced, and exosomes were administered. Histological analysis (HE and Nissl staining), motor function tests (BBB score and horizontal ladder), TUNEL assay, immunofluorescence, ELISA, and Western blotting were performed to evaluate neuronal repair, inflammation, oxidative stress, apoptosis, and signaling pathways. Results: SCI resulted in neuronal degeneration, impaired growth, increased apoptosis, and inflammation. BMMSC-derived exosomes overexpressing miR-34b-5p significantly improved neuronal survival (p<0.01), reduced apoptosis (p<0.01), and mitigated inflammation and oxidative stress (p<0.05) compared to controls. Enhanced M2 polarization of microglia was observed (p<0.01), alongside inhibition of the MAPK pathway and activation of the PI3K/Akt pathway (p<0.01). Conclusion: BMMSC-derived exosomes overexpressing miR-34b-5p regulate MAPK and PI3K/Akt pathways, promoting M2 microglial polarization, reducing inflammation and lipid peroxidation, and protecting against neuronal apoptosis in SCI. The findings underscore their efficacy as a therapeutic strategy for SCI.
Keywords: Bone marrow mesenchymal stem cells; Exosome; MiR-34b-5p; Spinal cord injury; MAPK/PI3K/Akt pathway